The death penalty in the United States of America: challenging the constitutionality and analyzing inconsistency of the Supreme Court justices - Gumeņuks, Andrejs (Riga Graduate School of Law, 2019)
The paper is focused on two issues: the constitutionality of the death penalty and inconsistency of justices of the Supreme Court of the United States. The paper aims at finding out how the constitutionality of the death penalty was challenged and whether or not were justices of the Supreme Court inconsistent in their opinions. In order to answer the research question, the author analyzes the cases of the Supreme Court of the United States. The cases touch upon issues of the death penalty for rape, kidnapping, juveniles, mentally ill persons. The landmark cases, which stopped and then renewed the executions, will be analyzed.
Keywords: Human rights; United States of America; Supreme Court; Death penalty